Simulation and Experimental Investigation of Granular Medium Forming Technology on Titanium Alloy Sheet at 500 °C - Gaoshen Cai; Jubo Fu; Chuanyu Wu; Kangning Liu; Lihui Lang (Metals, 2021)
To investigate and verify the degree to which the forming properties of low plasticity materials are improved at room temperature using the granular medium forming (GMF) process at 500 °C, a coupled Eulerian–Lagrangian unit calculation model was established and a special mold was designed to conduct a GMF experiment for titanium alloy sheets under different-shaped pressing blocks. Then, using a three-coordinate measuring machine, the sizes of the outer contours of the parts formed at room temperature were measured, and the results showed that the bottom of the parts maintained a smooth surface during the drawing process. As the drawing height increased, the radius of curvature of the cambered surface gradually decreased. By measuring the wall thickness of the parts at different positions from the central axis using a caliper, the wall thickness distribution curves of these parts were obtained, which showed that the deformations of the bottom of the formed parts were uniform and the uniformity of the wall thickness distribution was good. By comparing the GMF experimental data at 500 °C with traditional deep drawing experimental data, it was found that the GMF technology could improve the forming properties of low plastic materials such as titanium alloys.